Aproximación al contenido del convenio en la Ley Concursal (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Provision is made in the new Bankruptcy Law for two solutions to situations of insolvency: agreement and liquidation. This bankruptcy agreement represents a means of resolving the debtor’s insolvency by reaching an agreement at the heart of the proceedings, sanctioned by the authorities and aimed at paying back loans while continuing the business or professional activity of the bankrupt. This new legislation serves to bring the Spanish legal code in line with European and International Law. Despite the legislator’s aim to cover all eventualities in this reform, there is still room for debate and the question regarding the need to regulate extra-judicial mechanisms to resolve crisis situations through this law remains unanswered.